Math Education in Intercultural Contexts : a logical-mathematical interpretation for duality Kaingang Kame-Kairu - Bernardi, Luci (Universidade Estadual Paulista. Faculdade de Ciências, 2021)
The aim of this paper is to present the results of research carried out in a Mathematics and Science training program for indigenous teachers of the Kaingang ethnic group by the Unochapecó in the municipality of Chapecó, Santa Catarina, Brazil. Based on the paradigm of ethno mathematics, one of the objectives of the program is to look for relations between traditional indigenous thinking and classical mathematics. We propose an analogy between logical-mathematical binary calculation systems and the Kaingang thought system expressed in its social organization and supported by two opposite and complementary dual categories: Kamé-Kairu. Our hypothesis postulates a certain similarity between the binary logic used for example, in logical circuits, and the binary system with which the traditional Kaingang culture encodes its social, natural, and even supernatural world. The binary pair Kaingang, Kamé-Kairu serves to codify relations of kinship, exchange, and alliances of the tribe, as well as the natural world that surrounds them. The analogy formulated provides interesting information for mathematical and scientific education in intercultural contexts.

O objetivo deste artigo é apresentar os resultados de uma pesquisa realizada em um programa de formação em Matemática e Ciências para professores indígenas da etnia Kaingang pela Unochapecó, no município de Chapecó, Santa Catarina, Brasil. Baseado no paradigma da etnomatemática, um dos objetivos do programa é buscar relações entre o pensamento indígena tradicional e a matemática clássica. Propomos uma analogia entre os sistemas de cálculo binário lógico-matemáticos e o sistema de pensamento Kaingang expresso em sua organização social e apoiado por duas categorias opostas e complementares: Kamé-Kairu. A hipótese postula certa semelhança entre a lógica binária usada, por exemplo, nos circuitos lógicos, e o binarismo com o qual a cultura Kaingang tradicional codifica a relação de parentesco, troca e alianças da tribo, bem como o mundo natural que os rodeia. A analogia proposta pode fornecer informações interessantes para a educação matemática e científica em contextos interculturais.
Educação Matemática em Contextos Interculturais: uma interpretação lógico-matemática para a dualidade Kaingang Kamé-Kairu.
Keywords: Ciencias Sociales; Ciencias de la Educación